Optimization of selective copper extraction from chalcopyrite concentrate in presence of ammonium persulfate and ammonium hydroxide - Turan, Mehmet Deniz (Springer, 2019)
The dissolution of copper and iron from chalcopyrite concentrate in the presence of ammonium persulfate (APS) and ammonium hydroxide was investigated under atmospheric leaching conditions. Experiments were designed by central composite design (CCD). Under the optimum leaching conditions ((NH4)(2)S2O8 concentration = 328 g/L; NH4OH addition = 16vol%; leaching temperature = 321 K (48 degrees C); leaching time = 120 min; liquid-to-solid ratio = 16; stirring speed = 400 r/min), selective leaching was achieved. 98.14% of the copper was leached, whereas iron did not pass into the solution. X-ray diffraction analysis of the leaching residue showed that iron compounds were predominant. Given the leaching results, the fact that the leaching process does not include uneconomical leaching stages such as extended milling/mechanical activation or high pressures/temperatures, and the low copper dissolution conditions, the attained selective leaching yield may be remarkable.
Keywords: leaching; complex reaction; selectivity; copper; chalcopyrite